Semi-active Suspension Control Improved Vehicle Ride and Road Friendliness - Guglielmino, Emanuele; Sireteanu, Tudor; Stammers, Charles W.; Gheorghe, Ghita; Giuclea, Marius; SpringerLink (Online service) (London : Springer London, 2008)
Semi-active Suspension Control provides an overview of vehicle ride control employing smart semi-active damping systems (controlled dissipative elements which only require low energy input). These systems are able to tune the amount of damping in response to measured vehicle-ride and handling indicators. Two physically different dampers (magnetorheological and controlled-friction) are analysed from the perspectives of mechatronics and control. Ride comfort, road holding, road damage and human-body modelling (nonlinear visceral response in particular) are studied. A multidisciplinary approach is adopted throughout the book. Sound mathematical modelling is balanced by a large and detailed section on experimental implementation, where a variety of automotive applications are described offering a well-rounded view of the application of such systems. The implementation of control algorithms with regard to real-life engineering constraints is emphasised. The applications described include semi-active suspensions for a saloon car, seat suspensions for vehicles not equipped with a primary suspension, and control of heavy-vehicle dynamic-tyre loads to reduce road damage and improve handling. Engineers and practitioners working in noise and vibration; automotive engineers working in vehicle design, research and development; biomechanical engineers, physicists and life-scientists interested in human-body responses to vibration; and graduate students in vehicle studies, mechanics of vibration, dynamics and control will find this book of material assistance in their work.
Dampers and Vehicle Modelling -- Human Body Analysis -- Semi-active Control Algorithms -- Friction Dampers -- Magnetorheological Dampers -- Case Studies.
Keywords: Engineering; Popular works; Vibration; Dynamical systems; Dynamics; Fluid mechanics; Automotive engineering; Control engineering; Robotics; Mechatronics; Biomedical engineering; Engineering; Automotive Engineering; Popular Science, general; Vibration, Dynamical Systems, Control; Control, Robotics, Mechatronics; Engineering Fluid Dynamics; Biomedical Engineering; Electronic books